Aplicações da espectroscopia Raman ao estudo dos efeitos de temperatura e de pressão hidrostática em cristais orgânicos: 2-amino-1,3,4- tiadiazol, 2-amino-5-fenil-1,3,4-tiadiazol e 2-amino-5-(4-deciloxi-fenil)-1,3,4- tiadiazol - Toledo, Thiago Andrade de (Universidade Federal de São Carlos, 2015)
Molecular organic crystals are a promising class of materials because of their excellent physical, chemical and biological properties. Among them, Thiadiazole and its derivatives have been investigated in the last years due their versatility to build new materials as well as their potential use in pharmaceuticals and organic electronic devices. For this reason, the temperature and hydrostatic pressure dependence on Raman spectra of the 2- amino-1,3,4-thiadiazol (ATD), 2-amino-5-phenyl-1,3,4-thiadiazol (APTD) and 2-amino-5-(4- decyloxy-phenyl)-1,3,4-thiadiazol (ADPTD) are investigated. In addition, complementary studies using FT-IR, thermal analysis as experimental technique and density functional theory (DFT) are also given in order to support the Raman analysis. Decreasing temperature, it can be observed the reduction of band line width and blue-shift (from 290 to 10 K), which allow a better identification of some vibrational modes, in special, in lattice mode region. In contrast, the temperature induces phase transition in the select molecular crystal above 373 K, in accordance with thermal analysis. Furthermore, pressure induces a molecular conformation changes at 0.8, 2 and 2.5 GPa in ADPTD characterized by appearance and disappearance of Raman bands. On the other hand, ATD and APTD show only anharmonic effects contribution.
Keywords: Cristal molecular; 1,3,4-tiadiazol; Efeitos anarmônicos; Transição de fase; Espectroscopia Raman; Molecular cristal; 1,3,4-thiadiazol; Anharmonic effects; Phase transition; Raman spectroscopy; CIENCIAS EXATAS E DA TERRA::FISICA